2015
DOI: 10.1152/ajpcell.00174.2014
|View full text |Cite
|
Sign up to set email alerts
|

Low-Mg2+ treatment increases sensitivity of voltage-gated Na+ channels to Ca2+/calmodulin-mediated modulation in cultured hippocampal neurons

Abstract: Culture of hippocampal neurons in low-Mg(2+) medium (low-Mg(2+) neurons) results in induction of continuous seizure activity. However, the underlying mechanism of the contribution of low Mg(2+) to hyperexcitability of neurons has not been clarified. Our data, obtained using the patch-clamp technique, show that voltage-gated Na(+) channel (VGSC) activity, which is associated with a persistent, noninactivating Na(+) current (INa,P), was modulated by calmodulin (CaM) in a concentration-dependent manner in normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It is known that Mg 2+ inhibits the ryanodine receptor (RyR) Ca 2+ -release channels by competing with Ca 2+ at the cytosolic activation sites of the channel in the mM range [31][32][33] and influences the fidelity of coupling between L-type Ca 2+ channels and RyRs [34]. On the other hand, cytosolic levels of H + , Ca 2+ , adenine nucleotides and Mg 2+ during fatigue influence the gating properties of the SR Ca 2+ channel [35], and the functional roles of the three main intracellular ions, Na + , Ca 2+ and Mg 2+ , are modulated by calmodulin connected voltage-gated Na + channels [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Mg 2+ inhibits the ryanodine receptor (RyR) Ca 2+ -release channels by competing with Ca 2+ at the cytosolic activation sites of the channel in the mM range [31][32][33] and influences the fidelity of coupling between L-type Ca 2+ channels and RyRs [34]. On the other hand, cytosolic levels of H + , Ca 2+ , adenine nucleotides and Mg 2+ during fatigue influence the gating properties of the SR Ca 2+ channel [35], and the functional roles of the three main intracellular ions, Na + , Ca 2+ and Mg 2+ , are modulated by calmodulin connected voltage-gated Na + channels [36].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study had shown that CaM overexpression in HEK1.1 cells increases the peak current of Na V 1.1 in a calcium-dependent manner [ 12 ]. Our previous study has also demonstrated that neuronal VGSC activity is modulated by CaM in a concentration-dependent manner in normal and low Mg 2+ condition [ 13 ]. Thus, we propose the following hypothetical model ( Figure 7 C) for the modulation of Ca 2+ /CaM/CaMKII on Na V 1.1 based on our present study and other studies [ 12 , 13 ]: At low [Ca 2+ ]ā€”a nonphosphorylated state of Ca 2+ concentrationā€”C-lobe is the predominant domain for apoCaM binding to IQ domain, and the binding of apoCaM to Na V 1.1 IQ is not affected by CaMKII.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has also demonstrated that neuronal VGSC activity is modulated by CaM in a concentration-dependent manner in normal and low Mg 2+ condition [ 13 ]. Thus, we propose the following hypothetical model ( Figure 7 C) for the modulation of Ca 2+ /CaM/CaMKII on Na V 1.1 based on our present study and other studies [ 12 , 13 ]: At low [Ca 2+ ]ā€”a nonphosphorylated state of Ca 2+ concentrationā€”C-lobe is the predominant domain for apoCaM binding to IQ domain, and the binding of apoCaM to Na V 1.1 IQ is not affected by CaMKII. At high [Ca 2+ ] but at a nonphosphorylated state of IQ domain, N-lobe becomes the predominant domain since some of the CaM binds with Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While NMDAR antagonists inhibit these forms of synaptic plasticity, AMPAR antagonists do not impair synaptic plasticity and do not inhibit memory formation or retrieval. Hippocampal hyperexcitability induced by magnesium reduction or removal is a well-suited in vitro model of epileptiform seizure activity to elucidate the cellular mechanisms that underlie epileptogenesis and the spontaneous recurrent epileptiform discharge activity associated with epilepsy [60]. The observed increase in spiking after the low magnesium treatment was significantly reduced after the addition of EGAR, indicating a rescuing effect of the agent.…”
Section: Discussionmentioning
confidence: 99%